2023
DOI: 10.1111/aen.12668
|View full text |Cite
|
Sign up to set email alerts
|

Female–female aggression in Bactrocera tryoni (Diptera: Tephritidae) and the influence of fruit quality on combat intensity

Bianca J. Kay,
Anthony R. Clarke

Abstract: Frugivorous tephritid (Diptera: Tephritidae) females compete over access to fruit for oviposition through aggressive interactions. These aggressive displays are for oviposition site maintenance to reduce the probability of subsequent larval competition. While female aggressive behaviours have been described for several frugivorous tephritid species, studies quantifying behavioural frequencies and sequences and examining how quality of the host fruit might modify the intensity of aggressive behaviours are minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In cases where competition between fruit flies has been known to cause changes in field host use patterns, one species will dominate in a given host, pushing a second species to host fruits that the first only irregularly uses (Charlery de la Masselière et al, 2017; Hassani et al, 2022): we did not observe this pattern. The positive correlation in the number of adults of both species reared from fruit also offers field data supporting the work of Kay et al (2024), who in laboratory studies found no interspecific larval competition between the species.…”
Section: Discussionsupporting
confidence: 82%
“…In cases where competition between fruit flies has been known to cause changes in field host use patterns, one species will dominate in a given host, pushing a second species to host fruits that the first only irregularly uses (Charlery de la Masselière et al, 2017; Hassani et al, 2022): we did not observe this pattern. The positive correlation in the number of adults of both species reared from fruit also offers field data supporting the work of Kay et al (2024), who in laboratory studies found no interspecific larval competition between the species.…”
Section: Discussionsupporting
confidence: 82%